The effectiveness of beetroot juice supplementation on exercise performance in sports: A systematic literature review - Petry, K. (Lithuanian University of Health Sciences, Medical Academy: Faculty of Nursing, Department of Sports Medicine, 2019)
Research aim: The aim of this literature review was to analyse recent studies (2014-2019) for the effects of beetroot juice supplementation in sports. Objectives: 1) To evaluate the effects of beetroot juice supplementation on sports performance; 2) To find the most effective protocol for beetroot juice supplementation in sports; 3) To evaluate the possible side effects from beetroot juice supplementation. Methodology: The database Pub Med was used to conduct this literature review, including studies and articles in English, not older than 5 years. The eligibility of the studies was determined by the PICO approach. Inclusion criteria: Population - The Subjects were healthy, aged between 19-44 years, both sexes. The athletic fitness varied from well-trained athletes to elite athletes. Intervention - All selected studies included supplementation with beetroot juice with different dosages. An exercise performance test was conducted after acute, chronic or acute + chronic BRJ supplementation. Comparison - placebo group. Outcome - changes in either mean power output (W), time trials (s), VO2max consumption, VO2average consumption or distance covered (m). All possible side effects mentioned and most appropriate dosing. Exclusion criteria: Population - Recreationally active and inactive subjects. Intervention - Combinations with other supplements. Comparison - Case reports, nitrate supplementation in other forms than BRJ. Outcome - Case studies, meta-analysis, no full text articles, literature reviews, effects on blood pressure, pulse, effects on diseases. Results: The study subjects were healthy, aged between 19-44 years, including both sexes. The athletic fitness of the subject included everyone from well-trained athletes to elite athletes, as specified by the study authors. A total of seventeen studies with 178 subjects (149 males, 29 females) were screened for possible sports performance effects, it was shown that in 130 subjects beetroot juice supplementation did not have any positive effect on mean power output, time trials, VO2max, VO2average oxygen consumption or distance covered (m). A positive effect was noted in 48 subjects on time trials, VO2max, VO2average consumption or distance covered, however no subject improved in mean power output. The quality of studies was ranked good in four, moderate in twelve and poor in one study. Conclusion:1) Beetroot juice was ineffective in 12 out of 17 studies in improving physical performance of trained athletes. However, positive effects on time trials, VO2max and VO2average were found on possible responders. 2) A dose of 15.2 mmol of nitrate 3 hours prior exercise appeared to be the most effective protocol in this literature review. 3) Beetroot juice does not have any serious side effects. Beeturia and GI disturbances, which subsided after stopping the supplementation were the only side effects noted. 4) Further studies are needed to evaluate the relationship between BRJ supplementation and type II muscle fibres, especially regarding the impact of the respective athlete`s physical fitness.